The role of Technetium-99m Sestamibi scintimammography to evaluate palpable breast lesions : a comparison with mammography and histological results - Nizami, Mohammad Athar Farooq (Division of Nuclear Medicine, 2018)
This study was conducted with the support of the Combined Breast Clinic at our institution which consists of the Departments of Surgery, Radiology and Radiation Oncology. The work was done in three parts. The literature showed somewhat lengthy imaging procedure for scintimammography which were not whole suitable to the setting of the Combined Breast Clinic. Initially a Pilot Study was conducted to determine the practicality of the imaging procedure. The results of this study were promising but the imaging procedure was time consuming. Certain modifications were subsequently done in the imaging method of the Formal Study to accommodate more number of patients into the study without jeopardizing the quality of the images. This study, however, had a shortcoming in that the way this study was structured one could not demonstrate lesion by lesion analysis of each breast lesion detected on clinical examination, mammography and scintimammography with their respective biopsy results. Our Formal Study and the literature suggested that scintimammography is of value in patients with indeterminate mammograms due to its high negative predictive value. Therefore, a separate Additional Study, with the same scintigraphic method, was conducted on patients with clinical breast lumps with indeterminate mammographic lesions. Special emphasis was placed on lesion by lesion comparison of each breast lesion detected by clinical examination or scintimammography or both with the biopsy results of that particular lesion.